Fostering Religious Moderation Values of The Sixth Graders in Sampang, Madura - Rusdiyanto , Rusdiyanto; Werdiningsih , Indah; Arisandi , Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2023)
The role of teachers in managing education is crucial for creating a conducive environment that fosters the development of religious moderation values. It goes beyond mere theoretical concepts within specific subjects or programs, aiming to achieve recognition that moderate education is being implemented. The objective of this research is twofold: 1) to analyze the cultivation of religious moderation values in sixth-grade learning at MI Miftahul Ulum Sampang, and 2) to describe the religious moderation values instilled in the sixth-grade students at MI Miftahul Ulum Sampang. This research adopts a qualitative descriptive methodology with a case study design. Data collection involves interviews, observations, and documentation. Data analysis proceeds through three stages: 1) condensing the data, 2) presenting the data, and 3) drawing conclusions and verifying findings. To ensure data validity, triangulation is employed, encompassing source triangulation, technique triangulation, and time triangulation. The findings of this research indicate that the cultivation of religious moderation values in sixth-grade learning at MI Miftahul Ulum Disanah Sampang encompasses various subjects, including thematic learning, Aqeedah (Belief) and Akhlaq (Morality), Quran and Hadith, Fiqh (Islamic Jurisprudence), Islamic Education, Science, Social Studies, and Arabic language. Furthermore, the religious moderation values identified in the sixth-grade students at MI Miftahul Ulum Disanah Sampang comprise tolerance, equality, moderation, peace, and nationalism.